2021
DOI: 10.1016/j.shaw.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review: Effectiveness of Interventions to De-escalate Workplace Violence against Nurses in Healthcare Settings

Abstract: Workplace violence (WPV) is an increasing cause of concern around the globe, and healthcare organizations are no exception. Nurses may be subject to all kinds of workplace violence due to their frontline position in healthcare settings. The purpose of this systematic review is to identify and consider different interventions that aim to decrease the magnitude/prevalence of workplace violence against nurses. The standard method by Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA, 2009)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 43 publications
7
72
0
Order By: Relevance
“…Managing violence and discrimination at workplace is an important issue that has been addressed by different intervention studies in the health care setting [ 54 – 58 ]. More or less effective interventions were identified such as training sessions and education programs (for example in communication skills) or organizational policies and practicies (such as introducing reporting systems or safety procedures, formulating no-tolerance policies, promoting people-oriented culture through open communication, cooperation, trust and participation in decision-making).…”
Section: Discussionmentioning
confidence: 99%
“…Managing violence and discrimination at workplace is an important issue that has been addressed by different intervention studies in the health care setting [ 54 – 58 ]. More or less effective interventions were identified such as training sessions and education programs (for example in communication skills) or organizational policies and practicies (such as introducing reporting systems or safety procedures, formulating no-tolerance policies, promoting people-oriented culture through open communication, cooperation, trust and participation in decision-making).…”
Section: Discussionmentioning
confidence: 99%
“…As the evidence focused on organizational interventions for preventing and minimizing aggression is still of low-quality, more studies in this area are needed [ 53 ]. A recent review proposed that to prevent patient aggression in healthcare organizations, the approaches should include multicomponent interventions, ideally involving all stakeholders [ 54 ] Our study showed that it is feasible to involve different stakeholders in joint initiatives to reach a shared understanding of the current situation and identify common problems, which might help to make new approaches more acceptable to different parties.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this occupational risk has significantly increased in terms of frequency and severity (Singh, 2017; Alsharari et al , 2021; Brunero et al , 2021; Somani et al , 2021) and has been exacerbated by the health crisis caused by the Corona Virus pandemic, in which healthcare workers are confronted with a large number of patients (Ramacciati and Giusti, 2020; Bhattacharjee, 2021).…”
Section: Introductionmentioning
confidence: 99%